Tingkat Kepuasan Masyarakat dalam Pengurusan Perizinan SIUP Agribisnis di Badan Pelayanan Perijinan Terpadu Satu Pintu dan Penanaman Modal Kota Denpasar - L. Mira Ambarasari Saka; IM. Narka Tenaya; IM. Sudarma (Universitas Udayana, 2014)
The primary function of government is to serve the public. To increase the public satisfaction is one of the efforts to improve the quality of public services. The service of trade business license (SIUP) for investing agriculture activities (agribusiness) is one of licensing service types that organized by BPPTSP and PM Of the Denpasar Municipality . The purpose of this study was to analyze the role of variables between the behavior of services and service standards to the satisfaction levels of public and influence the level of people's satisfaction with the use of an agency service in processing Agribusiness trade license (SIUP ) in BPPTSP and PM of the Denpasar Municipality. The number of samples was determined by 90 respondents who have had SIUP with agribusiness activity period of 2010 s/d 2013. Data Technical Analysis used Partial Least Square (PLS) with the Smart PLS program. The results showed that the behavior of the service variables have a correlation coefficient (r) of 0.956 with the value of the contribution (R2) greater than 0.914 standard variable satisfaction level of service to the public, showed a correlation coefficient (r) of 0.930 with the value of the contribution (R2) 0.865. Based on the result of R2 values, it means the better behavior of the service makes the higher level of public satisfaction. The good quality of service behavior will give an impact on the quality of service satisfaction. The Good quality of service behavior in BPPTSP and PM of Denpasar municipality will increase public satisfaction and encourage the Applicants to submit SIUP agribusiness independently. The level of public satisfaction proved positive and significant effect on service bureau services. It shown by the path parameter coefficients positive value of 0.859 with a statistic of 24.879 (t-statistic> 2.58), so that the level of public satisfaction has positive influence on the use of service bureaus in BPPTSP and PM of Denpasar municipality. The conclusion is although the public satisfaction in good level of service behavior but in reality the communities still using bureau services for helping to submit of agribusiness trade license . It caused the use of agency services are considered more practical.